Online assessments for accounting: Exploring students’ experiences and perceptions - Brink, S. M. (South African Journal of Higher Education, 2025)
South African Institute of Chartered Accountants (SAICA)-accredited universities aim to prepare students to pass the Initial Test of Competence (ITC) and there is mention that SAICA’s ITC might change to an online assessment in the future. This study investigated the possibility of introducing online accounting assessments at SAICA accredited residential universities by exploring students’ experiences of online assessments during the COVID-19 pandemic. In this qualitative study, a large South African residential university was selected as a single case. Fifteen accounting students were interviewed, and thematic analysis were used to analyse the data. The participants were not in favour of any form of online assessment for accounting, including online take-home assessments and online assessments written on campus in a venue equipped with reliable power supply and stable Internet connectivity under the supervision of invigilators. This study identified various issues and challenges based on accounting students’ experiences of online assessments during the pandemic and identified opportunities to reduce stress in an online assessment and to facilitate a more effective transition to online assessments. An understanding of the issues, challenges, and opportunities found by this study is useful for SAICA-accredited universities in the context of future online assessment development.